A NARRATIVE REVIEW: IMPACT OF DIETARY POLYPHENOLS ON METABOLIC SYNDROME MANAGEMENT - Julia Kuszneruk,; Katarzyna Krzemińska,; Maria Kubas,; Julia Czerwik,; Patrycja Felisiak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purposes: Metabolic syndrome includes central obesity, insulin resistance, dyslipidemia, and hypertension. Studies have explored polyphenols for their potential to prevent or manage these issues through antioxidant and metabolic effects.Materials and Methods: A comprehensive literature review was carried out utilizing PubMed and Google Scholar. The search incorporated keywords such as 'polyphenols', 'metabolic syndrome', 'visceral adipose tissue', 'insulin resistance', 'hypertension', 'atherogenic dyslipidemia'. The search included articles published from 2020 to 2025.Results: Although many studies suggest that polyphenols may help to manage central obesity, the effects of polyphenols on carbohydrate metabolism, blood pressure and lipid profiles are inconsistent and inconclusive. These conflicting results are probably due to small sample sizes and a lack of robust, high-quality human clinical trials.Conclusion: The review indicates a potential connection between dietary polyphenols and the individual elements of MetS, highlighting the need for further investigation in this area. Overall, due to the variability in study design and sample size, conclusions should be interpreted with careful consideration.